25 tahun Anugerah Bintang Popular BH (Kuala Lumpur : Berita Harian, 2013)
History of Anugerah Bintang Popular or Popular Star Award, an award presented annually by Berita Harian of Malaysia to recognize excellence of professionals in the entertainment industry, including the film and record industries.
In Malay.
Keywords: Anugerah Bintang Popular -- History; Celebrities -- Awards -- Malaysia; Entertainers -- Awards -- Malaysia; Celebrities in mass media